Selected peer-reviewed articles from the International Conference on Architecture and Built Environment 2016 (ICABE 2016), Kuala Lumpur, Malaysia, 5–6 October, 2016 - Mohamed Osman, Mariana; Abdullah, Muhammad Faris; Abdullah, Alias (American Scientific Publishers, 2017)
The theme of ‘Sustainable Well-Being in Architecture and Environmental Sciences,’ for this special section edition would be the platform for scholars, researchers, and practitioners from the Built Environment profession to share ideas and expand networking. I believe that this special section is timely to address concern on sustainable well-being, which is the pursuit of having a ‘good life’ within Earth’s carrying capacity. This pursuit involves addressing ‘well-being’ in a holistic way and adjusting to the planetary boundary and can evolve in many directions when explored in different contexts